Development Of Polyethylene Oxide Film Hydrogels With The Addition Of Banana Sap For Wound Dressing Applications - Fena Retyo Titani; Haryanto Haryanto (Universitas Muhammadiyah Purwokerto, 2020)
Hydrogels having been developed so far are those with polymer bases without any additives. For the acceleration of wound healing, it can be developed hydrogels with the addition of banana sap (Musa Paradisiaca) as a drug that is expected to accelerate the wound healing process. The preparation of Banana PEO-PEGDMA-Hydrogel Banana was made using a new method of dissolving banana juice with PEO-PEGDMA before crosslinking. The formulations of banana sap concentration used ranged from 0% to 15% (volume) and they were irradiated with gamma rays. The characteristics measured include gel fraction, swelling ratio, velocity of water vapor transmission and mechanical properties. The chemical and morphological structures were analyzed using the Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). The acceleration of wound healing speed was analyzed by invivo test. The results showed that the value of gel fraction, swelling ratio and velocity of water transmission of PEO-PEGDMA-Banana Gum hydrogel increased at a concentration of 0-15%. Hydrogel tensile strength decreased with the addition of banana sap and conversely the percentage of elongation of hydrogel increased with it. PEO-PEGDMA hydrogel film with the addition of banana sap has been proven to accelerate the wound healing through the Invivo Test. This shows that hydrogels can be developed from PEO-PEGDMA- Banana Sap which can be used as wound dressing.